A Influence Live Shopping Shopee to Interest Public Purchase - Eka Sri Mulyani; Ahmad Dzulfikri Budi Kusworo (Journal of Advances in Accounting, Economics, and Management, 2024)
At this time the live shopping phenomenon has created a new dynamic in purchasing a product. products online. Where Live shopping Shopee is an online shopping system that allows sellers and buyers to interact directly and in real time through the live feature shopping Which available on application shopee. Objective researcher do research namely For analyze like what is the influence live shopping shopee on interest public purchasing. Method Quantitative is method study Which used researcher in research This, with using a sample of 60 people. In addition, the data collection method used is distribution of questionnaires or surveys via online media whatsapp. Data processing and testing The hypothesis was conducted using the SPSS Version 20 software program. Results of the Regression analysis Simple Linear shows that Shopee Live shopping has a significant influence towards the public's purchasing interest, which is 71.5%. Based on these results, it can be concluded that if live shopping experience increase so in a way automatic interest Public purchases will also increase. However, if live shopping experiences a decline then automatically the public's interest in buying will also decrease. Therefore, the final result study show that Live shopping on application Shopee can increase interest purchase public.